2005
DOI: 10.1161/01.cir.0000164199.72440.08
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Venous Insufficiency

Abstract: C hronic venous disease is often overlooked by primary and cardiovascular care providers because of an underappreciation of the magnitude and impact of the problem. The importance of chronic venous disease is related to the number of people with the disease and the socioeconomic impact of its more severe manifestations. Unfortunately, the literature concerning the prevalence and incidence of chronic venous disease has varied greatly because of differences in the methods of evaluation, criteria for definition, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
294
2
24

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 457 publications
(323 citation statements)
references
References 73 publications
3
294
2
24
Order By: Relevance
“…Morphologically, the appearance of these veins is swollen and bulged and frequently accompanied by incompetent valves. Consequently, the increase in venous volume results in venous hypertension and thus a chronic increase in venous wall stress 2, 4. In this context, we showed that these environmental conditions activate the transcription factor activator protein 1 (AP‐1), which controls expression of genes with products that promote cellular activity and proliferation in the venous wall.…”
Section: Introductionmentioning
confidence: 99%
“…Morphologically, the appearance of these veins is swollen and bulged and frequently accompanied by incompetent valves. Consequently, the increase in venous volume results in venous hypertension and thus a chronic increase in venous wall stress 2, 4. In this context, we showed that these environmental conditions activate the transcription factor activator protein 1 (AP‐1), which controls expression of genes with products that promote cellular activity and proliferation in the venous wall.…”
Section: Introductionmentioning
confidence: 99%
“…This agrees with findings in our study where occupation with prolonged standing constituted the greatest majority of 20 (44.44%), (Figure 1). The secondary types have known causes, such as deepvein thrombosis, atriovenous fistula, pelvic mass(es), like pregnancy, tumours or previous pelvic surgeries causing adhesions, obesity, smoking, and gender [12][13][14]. The incidence of varicose veins is highly variable, fluctuating around factors such as age, sex and geography [14].…”
Section: Discussionmentioning
confidence: 99%
“…Существуют также инвазивные методы лечения (склеротерапия, радиоабляция, эндоваскулярная те-рапия, флеботомия и др.) [32].…”
Section: дополнительные методы исследованияunclassified